PERTANGGUNGJAWABAN NOTARIS TERHADAP KEABSAHAN AKTA PENGIKATAN JUAL BELI DIMANA ADA PIHAK YANG MENGGUNAKAN SURAT KUASA JUAL YANG TIDAK DILEGALISASI - MELLY MELLY (PREMISE LAW JURNAL, 2016)
Land sales contract drawn up by a Notary is a sales agreement in buying and selling. The problem is that he makes a sales contract by using Sales Contract Deed with compensation in which the seller uses delegated power of attorney to sell. In its implementation, the seller uses delegated power of attorney to sell and, after it has been examined, it is only the copy of an underhanded power of attorney to sell from the land owner. The seller promises to bring the original one since it is being sent; both parties and the Notary agree to carry out the sale of the land. The Notary gives the opportunity a few days for the seller to bring the original one and to take the copy of the Sales Contract Deed with compensation which has been signed. The research used judicial normative method which is the presentation of legal provisions related to legal theories as the object of the research and the implementation of law in society related to the object of the research. Keywords : Notary’s Responsibility, Deed for Buying and Selling